2018
DOI: 10.1155/2018/5157645
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Ketosis and Mitohormesis: Potential Implications for Mitochondrial Function and Human Health

Abstract: Impaired mitochondrial function often results in excessive production of reactive oxygen species (ROS) and is involved in the etiology of many chronic diseases, including cardiovascular disease, diabetes, neurodegenerative disorders, and cancer. Moderate levels of mitochondrial ROS, however, can protect against chronic disease by inducing upregulation of mitochondrial capacity and endogenous antioxidant defense. This phenomenon, referred to as mitohormesis, is induced through increased reliance on mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(130 citation statements)
references
References 403 publications
3
119
0
1
Order By: Relevance
“…This typically increases circulating ketone bodies (β-hydroxybutyrate (BHB) and acetoacetate (ACA) from concentrations that are typically less than 0.3 mM into the range of nutritional ketosis, which for BHB, we define as 0.5-3 mM (29). This range is below the typical 5-10 mM range for BHB that occurs during prolonged fasting, and well below concentrations characteristic of ketoacidosis (28,29,30). From the perspective of meeting energy demands, the reduced carbohydrate and moderate protein intakes necessarily make ketogenic diets high in fat.…”
Section: K E T O G E N I C D I E T Smentioning
confidence: 84%
See 1 more Smart Citation
“…This typically increases circulating ketone bodies (β-hydroxybutyrate (BHB) and acetoacetate (ACA) from concentrations that are typically less than 0.3 mM into the range of nutritional ketosis, which for BHB, we define as 0.5-3 mM (29). This range is below the typical 5-10 mM range for BHB that occurs during prolonged fasting, and well below concentrations characteristic of ketoacidosis (28,29,30). From the perspective of meeting energy demands, the reduced carbohydrate and moderate protein intakes necessarily make ketogenic diets high in fat.…”
Section: K E T O G E N I C D I E T Smentioning
confidence: 84%
“…In terms of trend diets using ketone bodies or the KD, the appetite-reducing effect is one of the most commonly cited advantages (30).…”
Section: K E T O G E N I C D I E T Smentioning
confidence: 99%
“…There is also a significant and accumulating body of evidence demonstrating a statistically significant reduction in oxidative and nitrosative stress and upregulation of cellular antioxidant defences in the brains of animals following prolonged dietary ketosis ( [106][107][108][109][110][111]; reviewed by [41]). This decrease would also appear to be clinically significant as several authors have reported a reduction in oxidative damage to neurones and increased neuronal survival as a result of dietary induced ketosis especially in an environment of cerebral glucose deprivation [109,[111][112][113].…”
Section: Consequences Of Ketogenesis and Ketolysis In The Cnsmentioning
confidence: 99%
“…This surge in mitochondrial activity is accompanied by a modest increment in free radical levels, which in turn prompts antioxidant defenses that reduce these levels to values below those seen before the intervention. The net effect is that the worms age more slowly and end up living twice as long as usual (see also Miller et al 2018;Schulz et al 2007).…”
Section: All Creatures Great and Smallmentioning
confidence: 99%